Restrictive strabismus and gaze-evoked oculocardiac reflex following pterygium repair with fibrin glue - Luai T Eldweik; Shaikha Aljneibi (SAGE Open Medical Case Reports, 2022)
Oculocardiac reflex is a phenomenon caused by traction applied to the extraocular muscles, or pressure on the globes. The afferent stimulus travels via the ophthalmic branch of cranial nerve V, and the efferent stimulus travels via cranial nerve X, which can cause severe bradycardia and potentially hypotension, atrioventricular block, ventricular ectopy, and rarely asystole. Oculocardiac reflex is different from vasovagal syncope which has another pathway, and is triggered by pain or emotional upset, that results in failure of autoregulation of blood pressure. Ophthalmologists often observe oculocardiac reflex intraoperatively upon manipulation of extraocular muscles during strabismus surgeries. We report a case with a previously undescribed complication following pterygium autograft with fibrin glue stimulating oculocardiac reflex resulting in episodes of sudden bradycardia associated with light headedness and nausea.